1991
DOI: 10.1111/j.2042-7158.1991.tb03538.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Prednisolone Sensitivities of the Endocrine System and Peripheral-blood Lymphocytes are Closely Related to Clinical Incidence in Renal Transplantation

Abstract: Endocrine- and immune-responses to prednisolone and their relation to clinical incidence were assessed in 19 renal transplant recipients. All of the patients were treated with prednisolone and cyclosporin. Response of the hypothalamic-pituitary-adrenal (HPA) system to prednisolone was evaluated by measuring serum cortisol concentration. Cortisol concentration before transplantation was 126.7 +/- 38.6 ng mL-1, while it decreased to 4.1 +/- 2.5 ng mL-1 within the period characterized by a cumulative dose of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Studies on the HPA axis sensitivity to GCs in young and elderly normal population have demonstrated that up to ten percent of normal subjects without DEX metabolism alterations can be considered glucocorticoid resistant, using no suppression of plasma and salivary cortisol after 1 mg DEX as end-point [18, 30 -32] . In an attempt to identify predictive factors of the response to GC, the pattern of DEX-mediated inhibition of Con-A stimulated PBMC proliferation has been used in different infl amma-tory and immune disease as asthma [34] , rheumatoid arthritis [35] idiopatic nephrotic syndrome [36] , and in patients awaiting renal transplantation [37] . These studies have demonstrated an increased incidence of lymphocyte resistance to the effects of GC in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the HPA axis sensitivity to GCs in young and elderly normal population have demonstrated that up to ten percent of normal subjects without DEX metabolism alterations can be considered glucocorticoid resistant, using no suppression of plasma and salivary cortisol after 1 mg DEX as end-point [18, 30 -32] . In an attempt to identify predictive factors of the response to GC, the pattern of DEX-mediated inhibition of Con-A stimulated PBMC proliferation has been used in different infl amma-tory and immune disease as asthma [34] , rheumatoid arthritis [35] idiopatic nephrotic syndrome [36] , and in patients awaiting renal transplantation [37] . These studies have demonstrated an increased incidence of lymphocyte resistance to the effects of GC in these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have also demonstrated the relationship between PBMC-response to GCs in vitro and the clinical efficacy of GCs in renal transplant recipients [16,26,39,40]. According to the findings of these reports, recipients whose PBMCs were relatively resistant to the blastogenesis-suppressing effects of GCs showed a significantly higher risk of acute rejection episodes or graft loss during GC therapy [16,26,39,40]. Similarly, renal transplant recipients who exhibited poor PBMC-responses to cyclosporine have also been reported to show unsatisfactory clinical outcomes when treated with cyclosporine [17,41].…”
Section: Organ Transplantationmentioning
confidence: 97%
“…Based on the data for healthy subjects, the normal range upper-thresholds of PBMCresponse to immunosuppressants were established, and according to these ranges it might be possible to single out patient populations who are refractory to therapy with these drugs [16,17]. Many reports have also demonstrated the relationship between PBMC-response to GCs in vitro and the clinical efficacy of GCs in renal transplant recipients [16,26,39,40]. According to the findings of these reports, recipients whose PBMCs were relatively resistant to the blastogenesis-suppressing effects of GCs showed a significantly higher risk of acute rejection episodes or graft loss during GC therapy [16,26,39,40].…”
Section: Organ Transplantationmentioning
confidence: 98%
“…Ten milliliters of the heparinized blood was loaded on 3 ml of Ficoll-Hypaque solution, centrifuged at 13OOg for 15 minutes, and PBMCs, including lymphocytes, were separated as described previously. [14][15][16]20721 The cells were washed and resuspended in RPM1 1640 medium that contained 10% fetal calf serum, 100,000 III/L penicillin G, and 100 mg/L streptomycin, to a final density of 1 X lo6 cells/ml.…”
Section: Isolation Of Peripheral Blood Lymphocytesmentioning
confidence: 99%
“…14-i7 In renal transplantation, recipients whose lymphocytes were resistant to glucocorticoids showed a high risk of acute allograft rejection or graft loss during glucocorticoid therapy. [8][9][10][11][12][13][14][15][16] Renal transplant recipients who exhibited poor lymphocyte response to cyclosporine have also been reported to show unsatisfactory clinical outcome when treated with cyclosporine. ",i8 It is therefore important to determine the distribution of the population of immunosuppressant "hyperresistant" patients, with the inclusion of glucocorticoids and cyclosporine, for several immunologic disorders and in organ transplant recipients.…”
mentioning
confidence: 99%